Wood density and ring width in Quercus rotundifolia trees in southern Portugal - Sousa, Vicelina (2021)
Quercus rotundifolia Lam., known as holm oak or evergreen oak, occurs naturally in the western Mediterranean region, mainly as part of the agroforestry or agrosilvopastoral systems in Portugal (“montado”) and Spain (“dehesa”), and is economically important for acorn production. Less attention has been given to Q. rotundifolia wood, and its density variability is not known, namely related to tree growth. The wood density of 20 Q. rotundifolia trees was measured along the radial direction by X-ray densitometry and the factors responsible for ring width and wood density variation within and between trees were investigated at two sites located within the main species region in southern Portugal. Ring width was significantly different between sites, with an average of 1.81 mm and 1.55 mm. Wood density was very high and averaged between 888 kg/m3 and 914 kg/m3 but not significantly different between sites. Ring width and wood density showed a positive and significant correlation at both sites. Cambial age was the main source of variation for ring width and wood density, while between-tree effects accounted for a considerable proportion of wood density variation. The results are an important contribution for the species valorisation aiming at high-value wood products, also adding knowledge on the species growth of interest for tree selection and sustainable management